Failure analysis of an involute spline coupling of an overhead bridge crane. (October 2019) - Monti, Stefano; Guagliano, Mario
Abstract: The present study concerns the failure analysis for a 15-tons bridge crane. In particular, the investigation is performed through a numerical simulation of the whole system, in order to extract the displacement reached when the system undergoes to the maximum in service payload. The failed element is one of the two spline coupling used for transmitting the torque from the gearbox to the drums, responsible for winding the cables. In addition, it is also presented an estimation of the wear phenomenon, by comparing the actual material performance with the once generally considered in literature. At the end, some advices to overcome the problem are introduced. Highlights: The spline contact pressure overcome the expected limits. The misalignment speeds up the damage on the spline teeth surface. Finite element model allowed to accurately determine in-service stress and strain. The material is too soft: hardening is suggested.